2013
DOI: 10.21002/jaki.2013.04
|View full text |Cite
|
Sign up to set email alerts
|

Riset Eksperimental Pengauditan: Evolusi Dan Topik Kontemporer

Abstract: Behavioral research in accounting is paying more attention to auditing issue since auditing relies heavily on judgment and decision making process. This article describes the development of experimental auditing research and identifies the potentials for contemporary research by documenting the international article from the 1970s to 2000s. This article is organized into the following sections. After the introductory part, it discusses the nature of experimental auditing research (EAP), the evolution of intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…motivation, experience, knowledge, ability) and the characteristics of fraud risk factors (general and specific) that influence the results of auditor's fraud hypotheses, fraud risk assessment, and the program audit. The focus in this study is that the study discusses variations in the assistance of fraud risk practices (based on an alternative fraud framework) that influences auditor's fraud risk assessment (Utami & Nahartyo, 2013). Specifically, this study uses various characteristics of auditor (such as level of experience and skepticism) to consider the extent to which fraud models influence an auditor's consideration of fraud risk factors.…”
Section: Risk Preferencesmentioning
confidence: 99%
“…motivation, experience, knowledge, ability) and the characteristics of fraud risk factors (general and specific) that influence the results of auditor's fraud hypotheses, fraud risk assessment, and the program audit. The focus in this study is that the study discusses variations in the assistance of fraud risk practices (based on an alternative fraud framework) that influences auditor's fraud risk assessment (Utami & Nahartyo, 2013). Specifically, this study uses various characteristics of auditor (such as level of experience and skepticism) to consider the extent to which fraud models influence an auditor's consideration of fraud risk factors.…”
Section: Risk Preferencesmentioning
confidence: 99%
“…This study is experimental research with a 2x2 inter-subjects factorial design. The main benefit of experimental research is that it explains the causal relationship between the observed dependent and independent variables (Utami & Nahartyo, 2013). The subjects are government internal auditors.…”
Section: Agency Theorymentioning
confidence: 99%
“…Accounting students are prospective accountants and auditors, making them suitable for our research subject. In experimental studies, students can act as subjects considering the task complexity between students and auditors (Utami & Nahartyo, 2013).…”
Section: Introductionmentioning
confidence: 99%